A Deep Diver's Becoming - Brown, Kevin (Université d'Ottawa / University of Ottawa, 2020)
When scuba diving under a physical overhead such as a cave, a mine, a shipwreck, or under a virtual overhead due to decompression requirements, it makes it impossible to safely access the surface in the event of an emergency. Therefore, diving with overhead is often described as technical diving. In this research, I address how technical divers in Outaouais, Quebec, practice this risky sport with unforgiving consequences. Based on fieldwork in Outaouais, I focus on divers, including myself, who perform trimix dives deeper than 200 feet. I argue that the process of becoming a deep diver is a lifelong journey where a diver learns to adapt to a milieu hostile to human life. The basic skills are acquired during classes to ensure that a novice diver will survive in this limit-environment. As divers bend the rules and take more risks to go deeper for longer lengths of time, they will go through a series of limit-experiences and near misses that are essential to their development and found to be regenerative. In turn, those limit-experiences and near-miss events shared with teammates create mutual trust. It is this trust that becomes the foundation of the team and allows the team to improve upon existing techniques and increase the depth and difficulty of their dives.
Keywords: Scuba diving; Technical diving; Anthropology; Rebreather; Trimix; Near miss; Limit experience; Deep diver; Scuba; Decompression